IMPLICATIONS OF COMMODIFIED PARWA SHADOW PUPPET PERFORMANCE FOR TOURISM IN UBUD, BALI - Gede Yoga Kharisma Pradana (Institut Pariwisata dan Bisnis Internasional, 2018)
The purpose of this article is to examine the phenomenon of Balinese shadow puppet performances as a tourism entertainment spectacle in Ubud, Bali. Basically, the Parwa shadow puppet shows as Balinese shadow puppets are stag for the purposes of traditional ceremonies with long duration. In contrast to the type of Parwa shadow puppet show in Ubud is stag for tourism, only it's stag with a shorter duration. This phenomenon certainly raises a big question about the implications of stag such performances for tourism.This article is prepared to use qualitative research methods. All data were obtained through literature study, interview and observation. After all data is obtained, it is analyzed by using the perspective of cultural studies.The results show that the commodification of Parwa shadow puppet shows for tourism has economic, social and cultural implications. Economically, the commodification of the Parwa shadow puppet show for tourism has already had implications for a change in instrumental value, adding profit to cottage owners and retailers. Socially, the commodity has implications in the popularity as well as the identity of shadows puppet group. Culturally has implications for the preservation of cultural identity in the context of tourism, mediation of cultural promotion to tourists, cultural degradation of puppets and the difficulty of enculturation.